Navigating terrains of war;youth and soldiering in guinea-bissau. - Henrik E. Vigh
Through the concept of "social navigation," this book sheds light on the mobilization of urban youth in West Africa. Social navigation offers a perspective on praxis in situations of conflict and turmoil. It provides insights into the interplay between objective structures and subjective agency, thus enabling us to make sense of the opportunistic, sometimes fatalistic and tactical ways in which young people struggle to expand the horizons of possibility in a world of conflict, turmoil and diminishing resources.